Synthesis and Crystal Structure of a Novel Hydrogen Bonded Supramolecular Complex Derived from Pyrimidine-2-sulfonate: [CuL2]?H2O - Dong, Hua-Ze; Bi, Wen-Tao; Zhu, Hai-Bin (Asian Journal of Chemistry, 2010)
A novel 3D supramolecular complex with a formula as [CuL2]·H2O, was formed by the reaction of 4-pyridine-2-yl-pyrimidine-2-sulfonate (NaL) with copper salt, in which metal ion was in a six-coordinated environments with a distorted octahedral geometry. Then independent mononuclear units are linked each other and pack in 3D-superamolecular network via hydrogen bonds and some π-π stacking interactions. The crystal is monoclinic, space group C2/c with unit cell parameters: a = 28.384(6) Å, b = 7.849(16) Å, c = 19.090(4) Å, α = 90º, β = 105.259(4)º, γ = 90º, V = 4103.1(15) Å3, Z = 8, Mr = 554.01, Dc = 1.794 g/cm3, μ = 1.327 mm-1, F(000) = 2248, R = 0.0405, wR = 0.0739 for 1970 reflections with I > 2σ(I).